Risk attitude and air pollution - Klingen, Joris,Ommeren, Jos van (Tinbergen Institute, 2020)
Medical research suggests that particulate matter (PM) increases stress hormones, therefore increasing the feeling of stress, which has been hypothesised to induce individuals to take less risk. To examine this, we study whether PM increases the probability of drawing in chess games using information from the Dutch club competition. We provide evidence of a reasonably strong effect: A 10µg increase in PM10 (33.6% of mean concentration) leads to a 5.8% increase in draws. Our results demonstrate that air pollution causes individuals to take less risk.
10419/220064
Keywords: Graue Literatur; air pollution; particulate matter; cognitive ability; risk taking